India Financial Sector Assessment Program : Basel Core Principles for Effective Banking Supervision - International Monetary Fund; World Bank (Washington, DC, 2018)
This assessment of the implementation of the BCP in India has been completed as part of the Financial Sector Assessment Program (FSAP), which has been undertaken by the International Monetary Fund (IMF) and the World Bank (WB) in 2017, at the request of the Indian authorities. The scope of the assessment is the scheduled commercial banks, and the assessment reflects the regulatory and supervisory framework in place as of the completion of the assessment. It is not intended to analyze the state of the banking sector or crisis management framework, which are addressed by other assessments conducted in this FSAP.